A new species of Phyzelaphryne Heyer, 1977 (Anura: Eleutherodactylidae) from the Japurá River basin, with a discussion of the diversity and distribution of the genus - Simões, Pedro Ivo; Costa, João Carlos Lopes; Rojas-Runjaic, Fernando J. M.; Gagliardi-Urrutia, Giussepe; Sturaro, Marcelo José; Peloso, Pedro L. V.; Castroviejo-Fisher, Santiago (Zootaxa, 2018)
We describe and name the second species of Phyzelaphryne (Brachycephaloidea, Eleutherodactylidae), from northwestern Brazilian Amazonia. Phyzelaphryne nimio sp. nov. is distinguished from its only congener, Phyzelaphryne miriamae, by its smaller body size and the anatomy of the carpal and metacarpal regions, with relatively larger (sometimes fused) supernumerary carpal and metacarpal tubercles. Molecular phylogenetic analyses based on fragments of the mitochondrial genes 16S rRNA and COI suggest that the currently known distribution of the species is restricted to its type locality and other areas within Estação Ecológica Juami-Japurá, state of Amazonas, Brazil. Based on molecular, morphological and bioacoustic evidence, we assigned other specimens recently collected in Parque Nacional do Jaú, state of Amazonas, Brazil, to P. miriamae, extending the species’ known geographic distribution north of the Amazon River.